Characterization of DLC/Si coatings under the influence of a simulated biological fluid - Vargas, William; Caballero-Gómez, José Luis; Aperador-Chaparro, Willian Arnulfo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
One of the metals most used as biomaterial is the 316LVM steel. Nevertheless, it presents complications when used as permanent implant, due to the metallic ion release to the surrounding tissues, leading to higher number of interventions that the patients must undergo. Given this problem, it was studied how to improve the conventional materials coatings behavior that can raise their mechanical and anti-corrosive properties, increasing their service life. This behavior was evaluated facing the micro-abrasion-corrosion of DLC/Si, coatings phenomena, deposited by using the assisted chemical vapor deposition by plasma in contact with the Ringer solution, simulating a biological environment. The results indicate that the coating experiences an increase in the wear volume, when is subjected to the micro-abrasion-corrosion mechanism, in comparison with the micro-abrasion test. Moreover, the most significant loss is found in the substrate without coating, which demonstrates the protective effect of the coating.